2010
DOI: 10.3109/08860220903391242
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV Infection in Continuous Ambulatory Peritoneal Dialysis and Hemodialysis Patients

Abstract: This is the first study that analyzes occult HBV prevalence in CAPD patients. We conclude that the prevalence of the occult HBV may be common in CAPD patients as in HD patients, and HCV positivity is not a contributing factor to occult HBV infection in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Similarly, 5 HBsAg positive patients were male and 2 were female. A study supports our results also showed high male to female ratio as HCV seropositive percentages over 4 year were ranged from (6.9-9.0%) in males and (5.3-8.5%) in females [14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, 5 HBsAg positive patients were male and 2 were female. A study supports our results also showed high male to female ratio as HCV seropositive percentages over 4 year were ranged from (6.9-9.0%) in males and (5.3-8.5%) in females [14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of OHB infection among renal dialysis patients ranged from 0-50% in previously published studies (Goral et al 2006, Altindis et al 2007, Stratta et al 2009, Aghakhani et al 2010, Motta et al 2010, Sav et al 2010). The wide range of OHB infection prevalence could be the result of many factors, such as the use of different assays for HBV-DNA detection, viral load (VL) fluctuation in this population and different geographic HBV prevalence among the studied regions.…”
mentioning
confidence: 92%
“…Current evidence indicates that there is a high prevalence of OHB infection among dialysis patients (Altindis et al 2007, Aghakhani et al 2010, Motta et al 2010, Sav et al 2010); however, the prevalence of OHB infection among kidney transplant recipients remains controversial, with few published data on this subject (Peres et al 2005, Bae et al 2012). …”
mentioning
confidence: 99%
“…Estudos comprovaram a existência de alta prevalência da IOB entre dialisados, entretanto a prevalência de IOB entre receptores de transplante renal é controversa 27,28,29,30,31,32 28,29 .…”
Section: Introductionunclassified
“…Pode originar-se tanto pela contaminação com sangue como pela doação de órgãos e funcionar como elemento desencadeador de reativação após uma hepatite, dependendo das características do vírus e de fatores do hospedeiro 30 .…”
Section: Introductionunclassified